Service Delivery Networks and Employment Relations at German Airports: Jeopardizing Industrial Peace on the Ground?. (12th October 2018) - Helfen, Markus; Sydow, Jörg; Wirth, Carsten
Abstract: In this article, we ask how organizational restructuring towards a network form of service delivery challenges an established form of employment relations in Germany, that is labour–management collaboration. Building on a theoretical discussion of the marketization hypothesis, we develop a structuration perspective on the relationship between network restructuring and labour–management collaboration, which highlights the political economy of inter‐firm networks. Empirically, we focus on two major airport authorities in Germany. Our findings show how these authorities at the core of service delivery networks face a strategic trade‐off between short‐term labour cost reductions and more adversarial employment relations. Apart from coinciding with a deterioration in working conditions for service workers, the handling of this trade‐off depends on managers' and worker representatives' commitment to collaboration across the network. While unions and works councils initially continued with social partnership‐type practices, the more adversarial management practices for enacting the network restructuring cause a fragmentation on the workers' side and increase the conflict potential. We conclude that the agency of management and worker representatives in the enactment of inter‐firm networks oscillates between more partnership‐like and more conflictive practices, which turn the network restructuring into a political process with divergent outcomes for employment relations.